2014
DOI: 10.1093/ckj/sfu111
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Renal Replacement Therapy (CORETH) project: study design and methods

Abstract: BackgroundTo date, research has neglected the patient's psychosocial and cognitive conditions as contributing factors to dialysis modality decision-making. Hence, the Choice of Renal Replacement Therapy (CORETH) study aims to examine these conditions with regard to their impact on the choice. Here we describe the design of the multicentre study, which is supported by a grant from the German Ministry for Education and Research.MethodsTwo groups of patients will be compared after having chosen peritoneal or haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…There were no significant differences with respect to the distribution of sex or duration of therapy. Furthermore, patients with missing CT data and patients with full CT data were compared regarding physical and psychosocial metrics from the CORETH Project (19). The comparison showed that patients with missing CT data were more comorbid; indicated a lower physical quality of life; lived more closely to the dialysis unit; had a smaller living space, a smaller social network, and fewer persons living in the same household; were less participation oriented; experienced poorer shared decision making; and were more likely to have depression ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no significant differences with respect to the distribution of sex or duration of therapy. Furthermore, patients with missing CT data and patients with full CT data were compared regarding physical and psychosocial metrics from the CORETH Project (19). The comparison showed that patients with missing CT data were more comorbid; indicated a lower physical quality of life; lived more closely to the dialysis unit; had a smaller living space, a smaller social network, and fewer persons living in the same household; were less participation oriented; experienced poorer shared decision making; and were more likely to have depression ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The project addresses the decision making for either HD or PD focusing on the perspectives of recently initiated patients on dialysis. Detailed information about the study design has been already published (16,19,20). Patients were recruited from May of 2014 to May of 2015 from 55 dialysis units all over Germany.…”
Section: Study Design and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…auch elektronisch anwend-und auswertbar (Handy, Computer). Darüber hinaus ist er in verschiedenen Settings des Versorgungsgeschehens einsetzbar und wird derzeit auch in einer weiteren multizentrischen Studie bei Patienten mit endgradigem Organversagen eingesetzt[27].Wir bedanken uns bei allenRehabilitanden für ihre Teilnahme. Des Weiteren möchten wir folgenden Kliniken für Ihre Expertise und Unterstützung danken: Eisenmoorbad Bad Schmiedeberg, Median-Klinik Kalbe/Milde, Paracelsus Klinik Am See-Bad Gandersheim, Paracelsus Klinik Bad Suderode, Teufelsbad Klinik Blankenburg, Waldburg-Zeil Klinik Bad Salzelmen, Gesundheitspark Bad Gottleuba, Rehabilitationsklinik an der Salza, Median-Klinik Bad Lobenstein, Fachklinikum Brandis, Rehabilitationsklinik Göhren, Rehabilitationsklinik Dahlener Heide.…”
unclassified